The Effect Vision Exercises on the improvement of Visual Attention Concentration and Serving Performance Accuracy in Tennis - Hafez, Abd alhalim (Journal of Physical Education, 2016)
The problem of the research lies in not including visual exercises in teachingprograms. The researcher aimed at preparing visual exercises and identifying their effect onimproving attention concentration and serving accuracy in tennis. The subjects were (40)female students from the college of physical education and sport sciences/ university ofBaghdad. The subjects were divided according to their sections into controlling group andexperimental group. The experimental program included pretests, followed by the teachingexercises and ended with posttests. The teaching program consisted of two teaching sessionsper week for two months making a total of (16) teaching unit. The data was collected andtreated using proper statistical methods. The researcher concluded that visual exercisescontribute to the learning and development of visual concentration and serving accuracy.